Design and modeling of graph theory approach based routing algorithm - Sivasankar, S.; Devasenapathy, Deepa; Madhumathy, P; Kaur, Gursimran; Sharma, Yogita; Rana, Prince (International journal on interactive design and manufacturing, 2024)
By concentrating on a product’s subsequent states as it moves through several phases, the product state idea gives a fresh viewpoint on manufacturing programmes. A theoretical example uses graph theory, a method with associated requirements for data organization to make use of the benefits of this notion offers. In a wireless sensor network, path selection for data routing with higher level of connectivity is of greater importance. A network’s structural representation is uniform in regular graphs. Regular graphs are a type of graph that is highly structured and provides complete network protection. Adjacent matrices are the most convenient way to represent a network’s connectivity. Here an algorithm for regularizing the nodes in a network using adjacency matrices is proposed. The proposed model is simulated using MATLAB to find out the centrality measure in terms of building connectivity between the sensor nodes with in the network.